SOSIALISASI DAN PENDAMPINGAN INOVASI SULAM PITA PADA MEDIA KERAJINAN PURUN DI KOTA BANJARBARU - Yuana Sukmawaty,; Dewi Anggraini,; Aprida Siska Lestia,; Nada Agustina,; Anita Khumaida,; Fatiya Hanifah,; Rabiatul Zannah,; Siti Jubaidah, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Purun woven is a local cultural inheritance that must be preserved its local wisdom. Currently, there are many product derivatives from this craft, one of which is a tote bag that is useful for reducing plastic waste when going shopping to malls and markets. This tote bag made from the purun swamp plant that grows around swamp and peat land in South Kalimantan Province is better known as the purun basket. The Micro, Small and Medium Enterprises (UMKM) and local creative industries, especially in Banjarbaru City, which has started to innovate with this purun basket has made the purun basket more widely known to foreign countries, including doing ribbon embroidery techniques on the purun basket media. Therefore, it is necessary to socialize this form of ribbon embroidery innovation to the public so that it is more widely known. This service aims to introduce additional skills in ribbon embroidery techniques to the administrators of the Women's Organization Association (GOW) of Banjarbaru City, as well as to increase the enthusiasm of the purun craftsmen in Banjarbaru City. The hope is that these skills can increase income for audiences that come from the administrators of the Women's Organization Association (GOW) of Banjarbaru City in spare time. The results of this service were enthusiastically welcomed by the management, who are also residents of the City of Banjarbaru and a special award among craftsmen because their work is widely recognized